A clinical study on the relationship between chronic rhinosinusitis and bronchial asthma - Kang, Jing; Yong, Hui; Zhang, Zhijuan; Liu, Jing; Gao, Xiaoping; Shao, Hui; Hou, Li (Frontiers in Medicine, 2024)
Objective To investigate the correlation between chronic rhinosinusitis (CRS) and bronchial asthma, focusing on the CRS without nasal polyps (CRSsNP) and CRS with nasal polyps (CRSwNP), as well as their impact on lung function. Methods A total of 141 patients diagnosed with chronic nasal-sinus inflammation were included in this study. Clinical data, including medical histories, nasal endoscopy scores, CT scores, symptom scores, and quality of life assessments, were collected. Results Among the patients with CRSsNP, 23.8% had concomitant bronchial asthma. The incidence of asthma was significantly associated with the severity of sinus involvement in CRSsNP patients (p = 0.049). Pulmonary function impairment was correlated with the severity of sinus inflammation in CRSsNP patients (p = 0.019). Quality of life was significantly affected in patients with concomitant asthma and CRSsNP or CRSwNP. Conclusion Chronic rhinosinusitis, both with and without nasal polyps, is closely correlated with bronchial asthma. Pulmonary function impairment is associated with the extent of inflammatory lesions in CRSsNP. Although CRSwNP does not significantly affect pulmonary function, the treatment of sinus diseases can contribute to the control of asthma.